1998
DOI: 10.1161/01.str.29.9.1888
|View full text |Cite
|
Sign up to set email alerts
|

Early Hemicraniectomy in Patients With Complete Middle Cerebral Artery Infarction

Abstract: Background and Purpose-Malignant, space-occupying supratentorial ischemic stroke is characterized by a mortality rate of up to 80%. Several reports indicate a beneficial effect of hemicraniectomy in this situation. However, whether and when decompressive surgery is indicated in these patients is still a matter of debate. Methods-In an open, prospective trial we performed hemicraniectomy in 63 patients with acute complete middle cerebral artery infarction. Initial clinical presentation was assessed by the Scand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
458
7
57

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 634 publications
(539 citation statements)
references
References 45 publications
(48 reference statements)
17
458
7
57
Order By: Relevance
“…Historically, there has been reluctance to perform this operation because of a high rate of mortality and profound morbidity in survivors. Until recently, only case series and nonrandomized case-control studies suggested any benefit of decompressive craniectomy [39][40][41][42][43]. Several recent randomized controlled trials have demonstrated improved survival after decompressive craniectomy in certain stroke populations [6,[44][45][46].…”
Section: Osmotherapymentioning
confidence: 99%
“…Historically, there has been reluctance to perform this operation because of a high rate of mortality and profound morbidity in survivors. Until recently, only case series and nonrandomized case-control studies suggested any benefit of decompressive craniectomy [39][40][41][42][43]. Several recent randomized controlled trials have demonstrated improved survival after decompressive craniectomy in certain stroke populations [6,[44][45][46].…”
Section: Osmotherapymentioning
confidence: 99%
“…The technique for decompressive haemicraniectomy is already well established 10,11 . It includes the A B remotion of a large (≥ 12 cm) bone flap with a circular or oval shape including the frontal, parietal, temporal and parts of the occipital squamae (with special care to avoid producing sharp bone edges); fixation of the dura at the edge of the craniectomy to prevent epidural bleeding; opening of the dura (usually one longitudinal and three radial incisions almost reaching the osseous rim) and placement of a dural patch made of lyophilised cadaver dura or more recently microporic poliester-uretane (Neuro-Patch ® ) in the incision.…”
Section: Discussionmentioning
confidence: 99%
“…In an open study 11 of 63 patients with complete MCA territoy strokes -with or without additional anterior or posterior artery territory infarction -those operated early (mean time from onset 21 hours, range 8 to 42 hours), had a 16%mortality rate. Only 4 of these 31 patients had signs of uncal haerniation with a unilaterally fixed and dilated pupil.…”
mentioning
confidence: 99%
“…A previous work has suggested that early craniectomy may be more effective since a reduction in mortality from 27% to 16% can be caused by stepwise reduction in time from 39 to 21 hours between surgery and stroke onset (Schwab, 1998).…”
Section: Introductionmentioning
confidence: 99%